Stakeholder Engagement and Determination of Priority Strategies in Quality Improvement in Higher Education - Sabban, Irawati; Herawan, Endang (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
Stakeholder management is vital to the project's success because the strategies, plans, methods and processes for stakeholders determine the success of implementing sustainable construction. This study aims to analyze the quality improvement of tertiary institutions in optimizing stakeholder involvement and determining quality improvement priority strategies. The research method used is qualitative, with the NVivo 12 application analysis. This research was conducted at the Pacific University (UNIPAS) Morotai. The study results show that through stakeholder involvement, Pacific University Morotai is committed to developing the potential of Morotai's human resources for the development and progress of the Morotai Island Regency area. As well as the proposed quality improvement priority strategy is also inseparable from the proposed derivative strategy in quality improvement within the Pacific University of Morotai itself. This derivative strategy can be effective, assuming the priority strategy can be implemented effectively.